2023
DOI: 10.1186/s13054-023-04466-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of macrolide treatment on long-term mortality in patients admitted to the ICU due to CAP: a targeted maximum likelihood estimation and survival analysis

Abstract: Introduction Patients with community-acquired pneumonia (CAP) admitted to the intensive care unit (ICU) have high mortality rates during the acute infection and up to ten years thereafter. Recommendations from international CAP guidelines include macrolide-based treatment. However, there is no data on the long-term outcomes of this recommendation. Therefore, we aimed to determine the impact of macrolide-based therapy on long-term mortality in this population. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…kos des Langzeitversterbens um ein Drittel gezeigt werden [18]. Über die letzten Jahre konnte mithilfe klinischer Studien gezeigt werden, dass eine kürzere Behandlungsdauer nicht von Nachteil für Patienten und Umfeld ist.…”
Section: Cme-fortbildungunclassified
“…kos des Langzeitversterbens um ein Drittel gezeigt werden [18]. Über die letzten Jahre konnte mithilfe klinischer Studien gezeigt werden, dass eine kürzere Behandlungsdauer nicht von Nachteil für Patienten und Umfeld ist.…”
Section: Cme-fortbildungunclassified
“…Even when Gram-positive sensitive pathogens usually cause CAP, guidelines suggest a broad-spectrum antibiotic empiric management in patients who require ICU 8 . In addition, dual therapy usually ensures coverage against atypical germs, improves the likelihood of initial adequate treatment, shortens the length of stay, and improves survival 20 , 32 34 . It is essential to point out that the prevalence of Pseudomonas aeruginosa as a causing pathogen of CAP in this cohort is 4.3% (88/2026) in all included patients and 18.2% (88/482) in those who had some identified micro-organisms which are comparable to the data generated in a multinational point prevalence study by Restrepo et alwhere they found a prevalence of 4.2% (133/3193) in the whole cohort and 11.3% (133/1173) among the culture-positive patients 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The definition of CAP was based on the diagnostic criteria proposed by the ATS/IDSA guidelines 8 . The inclusion criteria were patients older than 18 years, requiring admission to the ICU with an ICD-9/ICD-10 code of pneumonia within the top ten diagnoses in the discharge note, as published previously 20 . Moreover, patients must have received cefepime or piperacillin/tazobactam, which started during the first 24 h of ICU admission and must be continued for at least 72 h. Patients with infectious diagnoses other than pneumonia and those with ventilator-associated pneumonia were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org Infection with P. aeruginosa is linked to various infectious diseases, including sepsis, endocarditis, pneumonia, urinary tract infections, peritonitis, and other health hazards (Jacobs et al, 2020;Reyes et al, 2023). Recognized as one of the most formidable nosocomial pathogens, the treatment of P. aeruginosa infection poses a challenge due to the restricted array of available antibiotics (Bassetti et al, 2018).…”
Section: In Vitro Antioxidant Capacity Detection Of Cieo or Cidmentioning
confidence: 99%
“…Pseudomonas aeruginosa ( P. aeruginosa ), a Gram-negative rod-shaped bacterium affiliated with the Pseudomonadaceae family, is distinguished for its pathogenicity, especially in individuals with compromised immune function, thus establishing it as a notable opportunistic human pathogen ( Stover et al, 2000 ; Sathe et al, 2023 ). It has been reported that P. aeruginosa may cause various serious infections, including sepsis, endocarditis, pneumonia, urinary tract infections, peritonitis, and other health hazards ( Reyes et al, 2023 ). In studies focused on the innate immunity of C. elegans , P. aeruginosa is commonly used as a representative pathogen to investigate host-pathogen interactions, infection, and anti-infection mechanisms ( Yu et al, 2018 ; Martineau et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%